The Effect of Work Motivation, Work Discipline and Workload on Employee Performance at PT Batam Bahari Sejahtera - Hermanto Hermanto; Asron Saputra (LPPM Universitas Buddhi Dharma, 2025)
In today's era, competition between business actors is increasingly competitive, thus requiring every business actor to have quality resources in order to remain superior in facing challenges and competing with other competitors, changes in the business environment affect major companies in facing competition. This study aims to analyze the effect of work motivation, work discipline, and workload on employee performance at PT Batam Bahari Sejahtera. The population used is employees of PT Batam Bahari Sejahtera. This research uses a quantitative approach with sampling techniques based on saturated samples, with a total of 107 respondents. Data collection was carried out through the distribution of questionnaires and data analysis using data quality tests, such as validity tests, reliability tests, and classical assumption tests including normality tests, multicollinearity tests, and heteroscedasticity tests. The influence test involved multiple linear regression analysis and determinant coefficient analysis, while the hypothesis test involved the t-test. The results showed that work motivation had a positive and significant partial effect on employee performance, work discipline had a positive and significant partial effect on employee performance, workload had a positive and significant partial effect on employee performance, work motivation, work discipline and workload had a positive and significant simultaneous effect on employee performance.